Allelopathic effects and composition of aqueous extracts from different parts of Galinsoga parviflora Cav. on Medicago sativa L. and Avena sativa L - Shipu Cheng; Fanru Xu; Zhiyong Lu; Huairui Xu; Mengqi Cai; Juan Sun; Yufang Xu (PeerJ)
Background Galinsoga parviflora Cav. is a high-risk invasive plant that seriously threatens the development of grasslands in southern China. However, the allelopathic effects on Medicago sativa L. and Avena sativa L., which are widely cultivated forages around the world, have not been reported. Methods To explore the allelopathic mechanism of G. parviflora, the allelopathic effects of aqueous extracts from different parts of G. parviflora on M. sativa and A. sativa were investigated. The germination rate (GR), germination potential (GP), seedling height, fresh weight, and chlorophyll content of M. sativa and A. sativa seedlings were measured to elucidate the allelopathy of G. parviflora on the two forages. Based on the five indicators, synthetical allelopathic effects (SAE) of extracts was also calculated. In addition, the allelopathic components of the extracts in G. parviflora were quantitatively revealed by untargeted metabolomics detection. Furthermore, two key allelopathic substances, 1,4-cyclohexanedicarboxylic acid (CHDA) and trehalose, were selected to explore the inhibitory effect on two notorious weed species in China, such as gramineous Digitaria sanguinalis L. and broad-leaved Amaranthus retroflexus L. Result (1) The inhibitory effects of aqueous extracts from different parts of G. parviflora on recipient plants were different, the root was the weakest, and the whole plants was the strongest, with the values of synthetical allelopathic effects (SAE) on M. sativa at the highest concentration being −0.12 and −0.40, respectively. (2) Compared with A. sativa, M. sativa was generally more susceptible to the extracts. (3) The differences in the content of CHDA or trehalose might be a reason why extracts from different parts of G. parviflora exhibited different allelopathic effects. (4) The herbicidal activity test of key allelopathic substances found that CHDA has a strong inhibitory effect on the germination of D. sanguinalis and almost does not affect M. sativa and A. sativa. Thus, this discovery not only revealed allelopathic effects and components in different parts of G. parviflora, but provided scientific evidence for weed control based on natural plant extracts in the future.